Palestinian-Israeli Communications (1948–1988) (Eurasian Journal of History, Geography and Economics, 2023)
This study examines Palestinian-Israeli communications during the period from 1948 to 1988. The study focuses on the role of the Palestinian Liberation Organization (PLO) in the wars between the Palestinian people and the Zionist entity. It also discusses the First Palestinian Intifada from 1987 to 1993 (the Stone Intifada) and the Second Palestinian Intifada in the year 2000 (the Al-Aqsa Intifada), their causes, the conferences held during those times, and concludes by presenting the key findings of the research along with a list of important sources and references that were utilized in this study. When discussing Palestinian-Israeli communications, it becomes evident that since the establishment of the Zionist entity in Palestine, these communications between Palestinians and the Zionist entity have been marked by hostility. These communications have witnessed wars at times and peace agreements at others. During the period from 1948 to 1988, Israel managed to occupy vast areas of Palestinian territory, culminating in the complete occupation of Palestinian lands after the defeat of the Arabs in the 1967 war (the Naksa). Subsequently, Palestinian-Israeli communications alternated between peace and negotiation phases, with the Palestinian Authority becoming the second party to sign a peace agreement with the Zionist entity, as they both signed the Oslo Accords in 1993.